Specific miRNAs Change After 3 Months of GH treatment and Contribute to Explain the Growth Response After 12 Months - Catellani, Cecilia; Ravegnini, Gloria; Sartori, Chiara; Righi, Beatrice; Lazzeroni, Pietro; Bonvicini, Laura; Poluzzi, Silvia; Cirillo, Francesca; Predieri, Barbara; Iughetti, Lorenzo; Giorgi Rossi, Paolo; Angelini, Sabrina; et al. (Frontiers in Endocrinology, 2022)
Context There is growing evidence of the role of epigenetic regulation of growth, and miRNAs potentially play a role. Objective The aim of this study is to identify changes in circulating miRNAs following GH treatment in subjects with isolated idiopathic GH deficiency (IIGHD) after the first 3 months of treatment, and verify whether these early changes can predict growth response. Design and Methods The expression profiles of 384 miRNAs were analyzed in serum in 10 prepubertal patients with IIGHD (5 M, 5 F) at two time points before starting GH treatment (t−3, t0), and at 3 months on treatment (t+3). MiRNAs with a fold change (FC) >+1.5 or <-1.5 at t+3 were considered as differentially expressed. In silico analysis of target genes and pathways led to a validation step on 8 miRNAs in 25 patients. Clinical and biochemical parameters were collected at baseline, and at 6 and 12 months. Simple linear regression analysis and multiple stepwise linear regression models were used to explain the growth response. Results Sixteen miRNAs were upregulated and 2 were downregulated at t+3 months. MiR-199a-5p (p = 0.020), miR-335-5p (p = 0.001), and miR-494-3p (p = 0.026) were confirmed to be upregulated at t+3. Changes were independent of GH peak values at testing, and levels stabilized after 12 months. The predicted growth response at 12 months was considerably improved compared with models using the common clinical and biochemical parameters. Conclusions MiR-199a-5p, miR-335-5p, and miR-494-3p changed after 3 months of GH treatment and likely reflected both the degree of GH deficiency and the sensitivity to treatment. Furthermore, they were of considerable importance to predict growth response.